Deletion of the miR172 target site in a TOE‐type gene is a strong candidate variant for dominant double‐flower trait in Rosaceae. (14th September 2018) - Gattolin, Stefano; Cirilli, Marco; Pacheco, Igor; Ciacciulli, Angelo; Da Silva Linge, Cássia; Mauroux, Jehan‐Baptiste; Lambert, Patrick; Cammarata, Elia; Bassi, Daniele; Pascal, Thierry; Rossini, Laura
Summary: Double flowers with supernumerary petals have been selected by humans for their attractive appearance and commercial value in several ornamental plants, including Prunus persica (peach), a recognized model for Rosaceae genetics and genomics. Despite the relevance of this trait, knowledge of the underlying genes is limited. Of two distinct loci controlling the double‐flower phenotype in peach, we focused on the dominant Di2 locus. High‐resolution linkage mapping in five segregating progenies delimited Di2 to an interval spanning 150 858 bp and 22 genes, including Prupe.6G242400 encoding an euAP2 transcription factor. Analyzing genomic resequencing data from single‐ and double‐flower accessions, we identified a deletion spanning the binding site for miR172 in Prupe.6G242400 as a candidate variant for the double‐flower trait, and we showed transcript expression for both wild‐type and deleted alleles. Consistent with the proposed role in controlling petal number, Prupe.6G242400 is expressed in buds at critical times for floral development. The indelDi2 molecular marker designed on this sequence variant co‐segregated with the phenotype in 621 progenies, accounting for the dominant inheritance of the Di2 locus. Further corroborating the results in peach, we identified a distinct but similar mutation in the ortholog of Prupe.6G242400 in double‐flower roses. Phylogenetic analysis showed that these two genes belong to a TARGET OF EAT (TOE)‐type clade not represented in Arabidopsis, indicating a divergence of gene functions between AP2‐type and TOE‐type factors in Arabidopsis and other species. The identification of orthologous candidate genes for the double‐flower phenotype in two important Rosaceae species provides valuable information to understand the genetic control of this trait in other major ornamental plants. Significance Statement: We used peach as a model to gain insight into the molecular basis of double flowers, an important trait in many ornamental plants. We propose that a deletion causes a TOE‐type transcription factor to escape miR172‐mediated repression, in turn resulting in an increased number of petals, as corroborated by results on the orthologous gene in rose.